Co-encapsulation of Tamoxifen and Curcumin in PLA Nanoparticles Increases the Antiproliferative Activity over B16-F10 Cells - Loriangela Marceli Dal Pozzo; Thaysa Ksiaskiewcz Karam; Laís de Almeida Campos; Celso Vataru Nakamura; Rubiana Mara Mainardes; Rafaela Rosa-Ribeiro; Najeh Maissar Khalil (Brazilian Archives of Biology and Technology)
Abstract Tamoxifen (TAM) and curcumin (CUR) are compounds investigated for cancer treatment; however, tamoxifen is associated with side effects, especially reducing red blood cells, and curcumin has low bioavailability. Therefore, combining these compounds in an encapsulation system represents a promising therapeutic strategy. Poly-lactic acid nanoparticles (PLA-NPs) containing CUR, TAM, and their combination (CUR-TAM) were prepared via emulsification-solvent evaporation. The encapsulation efficiency was similar for both CUR and TAM, whether encapsulated individually or together, with approximately 57% for TAM and 92% for CUR. The nanoparticles exhibited spherical morphology, with an average size of approximately 200 nm. Zeta potential values were -16 mV for TAM, -26 mV for CUR, and -17 mV for CUR-TAM. In vitro release studies over 120 hours revealed 57% release for CUR and 49% for TAM in the CUR-TAM NPs. Hemolysis testing at 96 hours showed low hemolytic activity for all NPs while the antiproliferative activity against B16-F10 cells demonstrated a significant reduction in cell viability with CUR-TAM NPs (23%), compared to 89% for TAM NPs and 41% for CUR NPs. Combining CUR and TAM in nanoparticles is promising, offering potential therapeutic benefits while minimizing adverse effects.